Hydraulic pressure augmented deep drawing process for large draw ratios - Thiruvarudchelvan, Sinnathamby. (2008)
A novel hydraulic-pressure augmented deep drawing process for the manufacture of very deep cups from sheet metal is being investigated, refined and developed.